R269C variant of ESR1: high prevalence and differential function in a subset of pancreatic cancers - Tomer Boldes; Keren Merenbakh-Lamin; Shani Journo; Eliya Shachar; Doron Lipson; Adva Yeheskel; Metsada Pasmanik-Chor; Tami Rubinek; Ido Wolf (BMC Cancer, 2020)
Abstract Background Estrogen receptor α (ESR1) plays a critical role in promoting growth of various cancers. Yet, its role in the development of pancreatic cancer is not well-defined. A less studied region of ESR1 is the hinge region, connecting the ligand binding and DNA domains. rs142712646 is a rare SNP in ESR1, which leads to a substitution of arginine to cysteine at amino acid 269 (R269C). The mutation is positioned in the hinge region of ESR1, hence may affect the receptor structure and function. We aimed to characterize the activity of R269C-ESR1 and study its role in the development of pancreatic cancer. Methods Transcriptional activity was evaluated by E2-response element (ERE) and AP1 –luciferase reporter assays and qRT-PCR. Proliferation and migration were assessed using MTT and wound healing assays. Gene-expression analysis was performed using RNAseq. Results We examined the presence of this SNP in various malignancies, using the entire database of FoundationOne and noted enrichment of it in a subset of pancreatic non-ductal adenocarcinoma (n = 2800) compared to pancreatic ductal adenocarcinoma (PDAC) as well as other tumor types (0.53% vs 0.29%, p = 0.02). Studies in breast and pancreatic cancer cells indicated cell type-dependent activity of ESR1 harboring R269C. Thus, expression of R269C-ESR1 enhanced proliferation and migration of PANC-1 and COLO-357 pancreatic cancer cells but not of MCF-7 breast cancer cells. Moreover, R269C-ESR1 enhanced E2-response elements (ERE) and AP1-dependent transcriptional activity and increased mRNA levels of ERE and AP1-regulated genes in pancreatic cancer cell lines, but had a modest effect on MCF-7 breast cancer cells. Accordingly, whole transcriptome analysis indicated alterations of genes associated with tumorigenicity in pancreatic cancer cells and upregulation of genes associated with cell metabolism and hormone biosynthesis in breast cancer cells. Conclusions Our study shed new light on the role of the hinge region in regulating transcriptional activity of the ER and indicates cell-type specific activity, namely increased activity in pancreatic cancer cells but reduced activity in breast cancer cells. While rare, the presence of rs142712646 may serve as a novel genetic risk factor, and a possible target for therapy in a subset of non-ductal pancreatic cancers.